Pengaruh Kepemimpinan Kepala Sekolah dan Kompetensi Pedagogik Guru PAI terhadap Hasil Belajar Siwa Kelas VIII SMP Swasta Se-Kecamatan Leuwisadeng Kabupaten Bogor - Sucirama Sucirama; Imam Tholkhah (Jurnal Dirosah Islamiyah, 2020)
This study aims to determine whether or not the influence of the Principal's Leadership Leadership and Pedagogical Competence of PAI Teachers Against Student Learning Outcomes of Class VIII Private Schools in Leuwisadeng District, Bogor Regency. This research method is a quantitative method. This research is a radom sampling study because the population of 495 is taken from 15% of the total sample, namely 74 respondents. To get empirical data on variable X (students' perceptions of teacher competency) and Y variables (student learning outcomes) that is done by questionnaire or questionnaire. The Principal's leadership covers the Cognitive element, which is managing the school effectively and implementing a daily program. The apective element is able to motivate students to discipline in learning and work and achievement and the Psychomotor element is maintaining a student-centered learning climate. In PAI Teacher Pedagogical Competence has a cognitive element that is mastering the theory and principles of learning that educates, learning activities that educate and evaluate or evaluate, the apective element takes over the characteristics of students and the psychotoric element is communication with students and the development of potential students. while the Learning Outcomes have a cognitive element that is curiosity of students, dare to experiment and academic values, apective elements namely attitudes toward teachers and friends, class attendance and responsibilities towards homework, psychomotor elements namely self-actualization. From the results of the comparison of the Principal Leadership Variable significance value of 0.10> 0.05 means significant and obtained T count (2,652) and t table (1,993) then T arithmetic> T table means there is an influence between the principal's leadership on student learning outcomes. From the results of the PAI Teacher Pedagogical Competence variable the comparison of significance values ​​.17> 0.05 means significant and obtained the value of T arithmetic (22,439) and t table (1,993) then T arithmetic> T table means there is an influence between PAG Teacher Pedagogic Competence on student learning outcomes. From the comparison of F arithmetic 23.508 F table 3.12 then F arithmetic> F Principal Leadership and Pedagogical Competence of PAI Teachers jointly affect the learning outcomes of Class VIII (Eight) SMP students in Leuwisadeng District, Bogor Regency. Keywords: Learning, Teacher, School Principal, Leadership, Pedagogic, Students